2022
DOI: 10.1590/1807-1929/agriambi.v26n4p266-273
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate classification of cotton cultivars tolerant to salt stress

Abstract: Two multivariate methods were adopted to classify salt-tolerant cotton genotypes based on their growth and physiological traits. The genotypes were cultivated in a greenhouse and subjected to 45 days of irrigation with saline water from the V4 phase onwards. Irrigation was performed with saline water with electrical conductivity (ECw) of 6.0 dS m-1. A factorial-randomized block design was adopted with nine cultivars, two treatments of ECw (0.6 as the control, and 6.0 dS m-1), and four replicates. Plants were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…As every cellular response involves a chain of events, the metabolism in tolerant plants is expected to be faster, giving them better adjustment in situations of internal adversity (Marcelino et al, 2022;Braz et al, 2019). In sensitive plants, these responses are slower, and supplementation of organic substances that are involved in osmotic adjustment or energy supply generally provides more effective contributions since they act as a support to overcome the negative effects of water restriction, while hydration is not reestablished (Barbosa et al, 2021;Shen et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…As every cellular response involves a chain of events, the metabolism in tolerant plants is expected to be faster, giving them better adjustment in situations of internal adversity (Marcelino et al, 2022;Braz et al, 2019). In sensitive plants, these responses are slower, and supplementation of organic substances that are involved in osmotic adjustment or energy supply generally provides more effective contributions since they act as a support to overcome the negative effects of water restriction, while hydration is not reestablished (Barbosa et al, 2021;Shen et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In the cultivars BRS Seridó and FM 966, the drop in A occurred as a result of high transpiration rates and reduced carboxylation efficiency over the period assessed. In a study by Marcelino et al (2022), who subjected those same cultivars to moderate salinity Tolerance of cotton plants to saline stress (6 dS m -1 ) for 35 days, the authors reported that the cultivars BRS Seridó, CNPA ITA 90, and BRS Rubi behaved as tolerant cultivars as a function of the adjustment seen in the gs, E, and A of plants under stress. Under the severe stress condition used in the present study, tolerance changed due to the greater accumulation of salts in the cells, affecting the A and iWUE.…”
Section: Free Proline and Gas Exchange In Cotton Cultivars Subjected ...mentioning
confidence: 99%